2011
DOI: 10.3892/or.2011.1588
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-205 functions as a tumor suppressor in human glioblastoma cells by targeting VEGF-A

Abstract: MicroRNAs (miRNAs) are endogenously small non-coding RNAs which are key post-transcriptional regulators of gene expression. Deregulation of miRNAs is common in human tumorigenesis. We report that miRNA-205 is significantly down-regulated in glioma cell lines and tissue specimens. Ectopic expression of miRNA-205 induces apoptosis, cell cycle arrest, impairs cell viability, clonability and invasive properties of glioma cells. We further demonstrate that miRNA-205 can specifically suppress expression of VEGF-A by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 35 publications
7
82
1
1
Order By: Relevance
“…In addition to miR-29b, the VEGF transcript is predicted to contain binding sites for multiple miRNA types (as highlighted in Fig. 2C), such as miR-145 and miR-205, the expressions of which are reduced in PCa and have been shown to regulate VEGF in other cancer types (Szczyrba et al 2010, Fan et al 2012, Yue et al 2012, Boll et al 2013. However, it remains to be determined how effectively these miRNAs repress VEGF translation in PCa.…”
Section: Post-transcriptional Regulation Of Vegf Signaling In Pcamentioning
confidence: 99%
“…In addition to miR-29b, the VEGF transcript is predicted to contain binding sites for multiple miRNA types (as highlighted in Fig. 2C), such as miR-145 and miR-205, the expressions of which are reduced in PCa and have been shown to regulate VEGF in other cancer types (Szczyrba et al 2010, Fan et al 2012, Yue et al 2012, Boll et al 2013. However, it remains to be determined how effectively these miRNAs repress VEGF translation in PCa.…”
Section: Post-transcriptional Regulation Of Vegf Signaling In Pcamentioning
confidence: 99%
“…Yue et al (2012) reported that miR-205 is a potential tumor suppressor in human glioblastoma cells by down-regulating the expression of VEGF-A via direct interactions with the putative miRNA-205 binding site at the 3′UTR site. As another mechanism of tumor suppression by miR-205, Dar et al (2011) reported that miR-205 suppressed cell proliferation by regulating the E2F1 protein in melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…10,17,25,28 In previous observations, we found that miR-205 was significantly downregulated in glioma cell lines and tissue specimens and that ectopic expression of miRNA-205 induces apoptosis and cell-cycle arrest and impairs cell viability, clonability, and invasive properties of glioma cells by directly targeting vascular endothelial growth factor A. 26 In addition, another group found that downregulation of miR-205 in tissues was associated with glioma progression. 9 As shown in the studies discussed above, miR-205 is associated with the occurrence and development of cancers.…”
mentioning
confidence: 97%
“…5,22 Based on our previous observations, microRNA 205 (miR-205) is significantly downregulated in glioma cell lines and tissue specimens. 26 Here, we investigated the diagnostic and prognostic potential of miR-205 in the serum of patients with glioma.…”
mentioning
confidence: 99%